MA3X : MA3X announcement, advertisement, audiovisual experience a multimedia community bulletin board - Cabarle, Francis George Carreon
Conventional bulletin boards (BB) usually look untidy, as people typically use pins and thumbtacks to add new announcements and advertisements (ads). Managing and updating announcements and ads to multiple and/ or remote BBs can be time consuming and inconvenient. An electronic equivalent of such BB, in contrast, could be easily updated and managed. In this paper design, development and implementation of an electronic BB system using an LCD monitor attached to a single board computer (SBC) is discussed. The SBC runs the software which displays and schedules announcements and ads. A web interface, where users can submit their content, is developed to make content management easier. The system also concurrently plays free videos from youtube.com for entertainment, along with announcements and ads, which it downloads at predefined schedules. Finally, the different socio-technical considerations made during the design, as well as the performance of the setup, are discussed.